THE INFLUENCE OF PRICE PERCEPTION, BRAND AWARENESS AND QUALITY PERCEPTION ON BUYING INTEREST IN CHAMP NUGGETS IN EAST JAVA WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Hamzah Lutfi; Rita Ambarwati Sukmono (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of price perception, brand awareness, and quality perception on consumer purchasing interest in Nugget Champ in East Java, with brand image serving as an intervening variable. Method: A quantitative research design was applied using questionnaires distributed to 100 respondents aged 18–55 years in East Java. The sampling technique used was probability sampling with a simple random sampling approach, and data analysis was conducted using the PLS-SEM method through SmartPLS 3.0. Results: The findings indicate that price perception, brand awareness, and quality perception each have a positive and significant effect on brand image, which in turn strengthens consumer purchasing interest. Brand image acts as a key mediating factor linking consumers’ cognitive evaluations to behavioral intentions. Novelty: This study contributes to marketing and consumer behavior literature by empirically validating the mediating role of brand image in the frozen food industry, offering practical insights for maintaining competitive advantage and consumer loyalty in an evolving lifestyle-driven market.